ANALISIS AGROINDUSTRI DAN PEMASARAN IKAN ASIN (SUDI KASUS DI DESA NELAYAN KECAMATAN BANGKO KABUPATEN ROKAN HILIR) - Fajar Fajar; Salman Salman; Tibrani Tibrani (DINAMIKA PERTANIAN, 2014)
Population growth and changes in consumption patterns have led to fish consumption tends to increase. Salted fish agroindustry have a good perspective, so that there is a necessary effort to improve the quality and guaranted supply to meet the needs of consumers who continue to increase. The purpose of research was to analyze the characteristics of entrepreneurs and profile of salted fish agroindustry, to know the use of factors of production and technology, to analyze cost of production, revenue, efficiency, and value added, and to recognize channels and marketing functions, costs, margins and marketing efficiency. The research was conducted by using a survey method with a number of sample of 10 entrepreneurs which was selected purposively. In addition, the amound of 3 wholesalers and 2 retailers were selected. The results showed that the entrepreneurs aged 44 years, received 9 years of education, had 8 years experience with 3 family members on average, and the businesses used their own capital. The production cost ranged from Rp 4,179,982.99 to Rp 6,795,417.42, yield ranged from 566.91 kg to 1,319.23 kg, net income ranged from Rp 4,045,566.25 to Rp 6,396,882.58, and efficiency ranged from 1.75 to 1.94 on average. The salted fish was marketed through two marketing channels and the second channel was the most efficient.